Video Domain Shifts and Hallucination Rates in InternLM-V2 and Gemini 1.5 Pro - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 12 peer-reviewed papers addressing the following research question: What is the impact of video domain shifts, such as from lectures to documentaries, on the hallucination rates of InternLM-V2 compared to Gemini 1.5 Pro when evaluated using generative metrics instead. 10 claims were extracted from source literature; 4 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 5.4/10. This repor
Machine-generated literature synthesis.